A Randomized, Double-Masked, Multicenter, Phase III Study Assessing the Efficacy and Safety of Brolucizumab versus Aflibercept in Patients with Visual Impairment due to Diabetic Macular Edema (KITE) - Garweg, Justus G. (Klinische Monatsblätter für Augenheilkunde, 2020)
Background Brolucizumab is a single-chain variable antibody fragment (scVF) that specifically binds to VEGF-A. The results of two large phase III, multicentre, randomized clinical trials comparing intravitreal treatment with Brolucizumab and Aflibercept in neovascular age-related degeneration demonstrated its potency in the treatment of neovascular age-related macular degeneration (nAMD).Methods The currently tested injected dose of 6 mg Brolucizumab results in a 11.2 – 13.3 times higher equivalent molar dose compared to Aflibercept 2 mg. Thus, it is conceivable that the effect of Brolucizumab in DME exceeds that of other currently used anti-VEGF agents with regards to effect durability; this was confirmed for nAMD in a phase I/II study.Results Approved anti-VEGF drugs have shown unprecedented success compared to laser treatment with regards to restoration of visual acuity and improvement of diabetic retinopathy severity scores for up to 5 years. The visual gains were sustained after the loading phase and a reduced number of injections were required after the first year independent of the treatment strategy. Compared to pan-retinal laser photocoagulation, the time to progression of DRP was markedly extended and was proven by better preservation of the visual field, prevention of severe vision loss, hemorrhagic complications, and the need for intraocular surgery.Conclusions The ongoing prospective, randomized, phase III clinical studies in DME, KITE, and KESTREL aim to confirm the non-inferiority of Brolucizumab 6 mg compared to Aflibercept 2 mg on a functional and morphological level as well as durability effect over 2 years.
Keywords: diabetic macular edema; DME; Brolucizumab; Aflibercept; intravitreal therapy; randomized clinical trial